Analisis Prosedur Penyimpanan dan Pengelolaan Arsip Surat Ukur Tanah di Badan Pertanahan Nasional Kabupaten Pesisir Selatan - Nurrachman, Herru; Marlini, Marlini (Program Studi Informasi, Perpustakaan, dan Kearsipan , Jurusan Bahasa dan Sastra Indonesia, 2018)
AbstractThe study of this research in about procedures for carrying out archival storage and management in the Badan Pertanahan Nasional Kabupaten Pesisir Selatan. The purpose is to describe about file storage procedures and archive management in the Badan Pertanahan Nasional Kabupaten Pesisir Selatan. This research was carried out by descriptive method by visiting directly to the Badan Pertanahan Nasional in Pesisir Selatan Regency to observe and conduct interviews. After the data has been analyzed, the conclusions explain several steps in the file storage and management procedures for records in the offices of Badan Pertanahan Nasional Kabupaten Pesisir selatan: (1) survey of archives; (2) recording the land measuring number; (3) sorting archives; (4) archive bindings; (5) submission of archives; (6) archive storage.Keywords: archive, procedures, storage.